2016
DOI: 10.1002/jbt.21828
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Onabotulinumtoxin A on testes of the growing rat

Abstract: Onabotulinumtoxin A (onabotA) is gaining wide medical use in children. The present study was planned to investigate the influence of its injection on the maturing testicular structures in rats. Immature rats were injected in the bilateral cremaster muscles by onabotA with three doses of (10, 20, and 40 U/kg) three times in a 2-week interval. The effect of these injections on fertility indices was examined. Levels of antisperm antibodies and several apoptosis parameters were also investigated. DNA content in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Botulinum toxins (BoNTs) are a class of fatal proteins, mainly produced by Clostridium botulinum , which causes muscle paralysis as they act by binding presynaptically to high-affinity recognition sites on the cholinergic nerve terminals and effectively prevents the exocytosis of ACh vesicles at the neuromuscular junctions [ 8 10 ]. While a trace amount of purified BoNT has been identified to yield long-lasting anti-ageing therapeutic benefits and mitigating neuromuscular defects in various illnesses [ 8 , 9 , 11 ], some toxicological reports indicated that cremasteric injection of BoNT (10–40 U/kg) induces cell death and impairs spermiogenesis in the testis of experimental animals [ 12 , 13 ]. However, a recent report revealed that intrascrotal injection of BoNT in adult men did not induce any obvious adverse effect [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Botulinum toxins (BoNTs) are a class of fatal proteins, mainly produced by Clostridium botulinum , which causes muscle paralysis as they act by binding presynaptically to high-affinity recognition sites on the cholinergic nerve terminals and effectively prevents the exocytosis of ACh vesicles at the neuromuscular junctions [ 8 10 ]. While a trace amount of purified BoNT has been identified to yield long-lasting anti-ageing therapeutic benefits and mitigating neuromuscular defects in various illnesses [ 8 , 9 , 11 ], some toxicological reports indicated that cremasteric injection of BoNT (10–40 U/kg) induces cell death and impairs spermiogenesis in the testis of experimental animals [ 12 , 13 ]. However, a recent report revealed that intrascrotal injection of BoNT in adult men did not induce any obvious adverse effect [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, few toxicological reports indicated that cremasteric injection of botulinum toxin (10, to 40 U/kg) induces cell death and impairs spermiogenesis in the testis of experimental animals [12,13], while a recent report indicates that intrascrotal injection of botulinum toxin in adult male did not induce any adverse effect [14]. Nevertheless, ample scientific evidence unequivocally points towards the positive episodes of a very mild dose of therapeutic botulinum toxin such as BOTOX® against various clinical complications including movement disorders, cognitive deficit and behavioral abnormalities [8,9,11,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%